GROWTH STRATEGY FOR PERTAMINA TO FOSTER GOVERNMENTâS GREEN-FUEL PROGRAM - Fauzi, Rahmat
The growth of Indonesian oil-fuel consumption predicted to keep rising and correlated with Indonesian economy and population growth is around 5% per year. Indonesia has been depending on oil-fuel import that’s become a major contributor for Indonesia trading deficit. Government begins to find alternative solution by launched the bio-fuel program in order to reduce dependency on high-priced fuel-importing and it is also to utilize of increasing palm oil production in Indonesia at the same time. Indonesia has been launched bio-diesel program by mandate mix Fatty Acid Methyl Ester (FAME) up to 20% to conventional diesel-fuel. While adding FAME to diesel-fuel is the simplest and most common way of responding to regulatory provisions, the quality of the products is quite poor when compared to diesel-fuel, making the mix of FAME is limited due to technical concern. Pertamina has been successful in the plant trial production of green-fuels through co-processing such as green-diesel by Hydroprocessing units in RU II Dumai and green-gasoline and green-LPG (Liquefied Petroleum Gas) products in the RFCC (Residue Fluid Catalytic Cracking) in RU III. Due to the government's mandate regarding to the green-fuel business plan, Pertamina is directly assigned to foster its business line which will focus on producing green-fuel even expected 100% (B100). This program aims to reduce fossil-fuel import activity and optimize domestic potential to maintain energy security in Indonesia. PESTEL and Poster's Five Force are used to analyze the external factors, and the VRIN framework, Value Chain Analysis is used for internal analysis that elaborates the existing conditions of the company. As the final step, it needs to identify the company's resource gaps and then formulate the strategy through the Resource Pathway Framework (RPF) and Diamond Analysis method. Based on the conclusion of analysis results, Pertamina’s brand reputation and human resource are categorized as competitive advantages which are also known as its strength, meanwhile there are four resources being gaps involving production technology, innovation, product price (P3), and feedstock availability. Therefore, those need to be find out the solution by applying recommended strategies that can be proposed to Government. Based on RPF, innovation resources can be developed by internal development program, production technology can be improved through basic contract, and meanwhile P3 and raw material supply is reckoned to be controlled by building alliances by strong collaboration between Pertamina and key stakeholders including Government, CPO Companies, oil palm plantation industrial, technology licensor, and academics.